First successful use of ampicillin-sulbactam for rare Streptococcus agalactiae-associated peritonitis in peritoneal dialysis: a case report and literature review - Berrocal, Carlos; Quintero-Romero, J. M.; Mejia, Luz; Zapata-Aristizábal, A.; Nati-Castillo, H. A.; Gaibor-Pazmiño, Alice; Izquierdo-Condoy, Juan S. (Frontiers in Medicine, 2025)
IntroductionPeritonitis is a major complication of peritoneal dialysis, most often caused by gram-positive cocci. Streptococcus agalactiae (Group B Streptococcus) is an exceptionally rare pathogen in this context.Case presentationWe describe a 64-year-old man with end-stage renal disease on long-term PD who developed refractory peritonitis due to S. agalactiae. Peritoneal fluid analysis revealed 525 leukocytes/μL (74% polymorphonuclear cells) and Gram-positive cocci. Cultures confirmed S. agalactiae, fully susceptible to all tested antibiotics. Despite intraperitoneal vancomycin, the patient showed no clinical improvement. Because of limited intraperitoneal antibiotic availability, intravenous ampicillin–sulbactam (1.5 g every 12 h) was initiated, combined with prophylactic oral fluconazole. Clinical resolution was achieved after 10 days, followed by four days of oral therapy. The peritoneal catheter was subsequently removed, and the patient transitioned to intermittent hemodialysis.ConclusionThis case represents the first documented success of intravenous ampicillin–sulbactam for S. agalactiae–associated peritonitis in PD. It expands the therapeutic options for this rare and challenging infection and highlights the importance of culture-guided management and adaptive treatment strategies, particularly in resource-limited settings where conventional intraperitoneal therapies may be unavailable.